Compressive Strength of Cement Mortar with white cement and limestone - Saadi Klak, Fadya; I. Abdulla, Aziz (International Journal of Engineering and Technology, 2018)
In this paper, the properties of cement mortar were studied after replacing part of the cement with other materials namely white cement, and limestone powder. The experimental test results were compared with normal cement mortar. Three kinds of mixtures were used. In the first type, cement was replaced with white cement only with differentÂ ratesÂ (5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, and 50%), the best ratio was determined, namely, the percentage that gave the highest value in the compression strength test, which is the compensatory ratio of 25%. In the second type of mixtures, a fraction of the cement was replaced with limestone powder only and with different rates (10%, 20%, 30%, 40%, and 50%). In the third type, cement was replaced by 25% white cement and different limestone powder ratio. Super-plasticizer (SP) was used with 1.5% rate. The compressive strength, absorption, the dry and wet density of all mixtures was measured. The results showed that the use of white cement instead of cement led to the production of cement mortar different in colors and better specifications, especially when the compensation rate was 25%. The results also showed that limestone powder gave a remarkable improvement in the properties of white cement mortar.Â Â